Knowledge, attitudes, and practices of laboratory biosafety among undergraduate students in a Malaysian public university: lab biosafety KAP among Malaysia undergraduates - Shamsol Kamal, Syaza Nasyitah; Mohd Shaharuddin, Norfazlina; Ahmad Yusof @ Hanafi, Hanani (International Islamic University Malaysia, 2025)
Background: Laboratory biosafety is comprised of a crucial set of rules and regulations to be followed by the laboratory users. However, students’ awareness of the biosafety regulations and practices is unknown since there is no current data on laboratory biosafety knowledge. Therefore, this study aims to evaluate the knowledge, attitude and practice (KAP) levels regarding laboratory biosafety among health sciences undergraduates and determine the factors influencing their knowledge. Methods: A modified and adapted questionnaire was administered to the voluntary respondent who fulfill the inclusion and exclusion criteria. The questionnaires which consist of 31 questions related to the knowledge, attitude and practice on laboratory biosafety were distributed through online platform and face to face approaches. Spearman’s test was used to determine the correlation between the KAP elements, while independent t-tests was used to assess the association between the knowledge and demographic background of the respondent including the gender and briefing status on laboratory biosafety. One way ANOVA and Kruskal Wallis was applied to compare the differences of biosafety knowledge across academic years and faculties, respectively. Results: A total of 388 students voluntarily participated in the study. The survey showed that the students have a moderate knowledge on laboratory biosafety whilst have a good attitude and practice towards it. While no significant correlation was found between knowledge and attitude (r=0.046, p=0.371), practice showed a moderate positive correlation with attitude (r=0.417, p<0.001) and weak positive correlation with knowledge (r=0.135, p=0.008). Knowledge levels were significantly associated with the year of study (p<0.001) and briefing status on laboratory biosafety (p=0.013). However, knowledge score did not differ significantly by gender or faculty. Conclusion: Undergraduate health science students exhibit moderate knowledge on laboratory biosafety, despite demonstrating good perceptions and adherence to biosafety practices. The observed knowledge gaps may be attributed to insufficient briefing on the subject. Improving laboratory biosafety education could enhance student’s preparedness for laboratory work throughout their academic programme.